2018
DOI: 10.3803/enm.2018.33.3.355
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Resolution of Hypertension after Adrenalectomy in Patients with Primary Aldosteronism

Abstract: BackgroundThe aim of this study was to investigate the factors associated with resolution of hypertension after adrenalectomy in patients with primary aldosteronism. A secondary aim was to describe our use of the contralateral ratio in adrenal venous sampling (AVS) in the setting of suboptimal successful cannulation rates.MethodsA retrospective review of patients who underwent AVS followed by unilateral adrenalectomy for primary aldosteronism was performed.ResultsComplete resolution of hypertension and hypokal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The median age and BMI were 43 years (18-73) and 27 kg/m 2 (20-46), respectively. The median duration of HTN was 2.3 years (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Median preoperative systolic and diastolic BP was 150 mmHg (110-249) and 98 mmHg (70-151) on 3 (1-8) antihypertensives.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The median age and BMI were 43 years (18-73) and 27 kg/m 2 (20-46), respectively. The median duration of HTN was 2.3 years (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Median preoperative systolic and diastolic BP was 150 mmHg (110-249) and 98 mmHg (70-151) on 3 (1-8) antihypertensives.…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that the ARS was not predictive of resolution in the French population given genetic and metabolic differences. The clinical success of adrenalectomy for PA was evaluated in the population of Singapore [ 8 ]. Loh et al studied 40 consecutive patients surgically treated for PA in a 10-year period.…”
Section: Discussionmentioning
confidence: 99%
“…However, for the PASO score and the Utsumi nomogram due to the relatively small number of external validation studies ( n < 4), we cannot draw definite conclusions regarding the generalizability and usefulness of these models in clinical practice. The ARS model is supported by stronger evidence compared with other scoring systems 13,14,17–21,31–41,43,48,49 and therefore we believe that it is an accurate and reliable prediction model which is the most user‐friendly and the least costly to identify long‐term high likelihood of CRH after adrenalectomy for UPA, particularly when adrenalectomy is adrenal vein sampling‐guided, regardless of imaging results 13 …”
Section: Discussionmentioning
confidence: 96%
“…A study by Loh et al [ 8 ] demonstrated that only a short duration of hypertension (≤6 years) and an ARS of 3 to 5 were associated with resolution of hypertension after adrenalectomy in 40 patients with PA in Singapore, in contrast to the results of previous studies of ARS [ 5 6 ]. In 376 Chinese patients with APA, only a duration of hypertension of ≥6 years and a level of plasma aldosterone ≥35 ng/dL were significant independent negative predictors for complete hypertension cure [ 9 ].…”
mentioning
confidence: 95%
“…11 C-metomidate positron emission tomography tracers were developed as an alternative to AVS because metomidate binds to steroidogenic enzymes, including CYP11B, and enzymes involved in the biosynthesis of aldosterone and cortisol, suggesting its suitability in adrenocortical functional imaging for the lateralization of APA [ 15 ]. The study by Loh et al [ 8 ] suggested that the contralateral ratio (CR) might be a useful alternative to AVS for considering surgery in the setting of unilateral cannulation of the adrenal vein, but their study acknowledged that many unanswered questions remained to be resolved and that prospective clinical trials must be conducted to determine appropriate cut-offs of the CR and the efficacy of the CR relative to AVS.…”
mentioning
confidence: 99%